Early Modern Disputations and Dissertations in an Interdisciplinary and European Context
1 online resource.
Keywords: From the sixteenth through to the eighteenth century, printed disputations were the main academic output of universities. This genre is especially attractive as it deals with the most significant cultural and scientific innovations of the early modern period, such as the printing revolution and the development of new methods in philosophy, education and scholarly exchange via personal networks. Until recently, academic disputations have attracted comparatively little scholarly attention. This volume provides for the first time a comprehensive study of the early modern disputation culture, both through theoretical discussions and overviews, and numerous case studies that analyze particular features of disputations in various European regions.